Discovery of Modified Amidate (ProTide) Prodrugs of Tenofovir with Enhanced Antiviral Properties - Kalčic, Filip; Zgarbová, Michala; Hodek, Jan; Chalupský, Karel; Dračínský, Martin; Dvořáková, Alexandra; Strmeň, Timotej; Šebestík, Jaroslav; Baszczyňski, Ondřej; Weber, Jan; Mertlíková-Kaiserová, Helena; Janeba, Zlatko (Journal of medicinal chemistry, 2021)
This study describes the discovery of novel prodrugs bearing tyrosine derivatives instead of the phenol moiety present in FDA-approved tenofovir alafenamide fumarate (TAF). The synthesis was optimized to afford diastereomeric mixtures of novel prodrugs in one pot (yields up to 86%), and the epimers were resolved using a chiral HPLC column into fast-eluting and slow-eluting epimers. In human lymphocytes, the most efficient tyrosine-based prodrug reached a single-digit picomolar EC50 value against HIV-1 and nearly 300-fold higher selectivity index (SI) compared to TAF. In human hepatocytes, the most efficient prodrugs exhibited subnanomolar EC50 values for HBV and up to 26-fold higher SI compared to TAF. Metabolic studies demonstrated markedly higher cellular uptake of the prodrugs and substantially higher levels of released tenofovir inside the cells compared to TAF. These promising results provide a strong foundation for further evaluation of the reported prodrugs and their potential utility in the development of highly potent antivirals.
Keywords: Hepatocytes; objevování léků; Stereoisomerism; kyseliny fosforečné; Hepatitis B virus; HIV-1; antivirové látky; Phosphoric Acids; Microbial Sensitivity Tests; fenol; tyrosin; hepatocyty; Prodrugs; stereoizomerie; Tyrosine; amidy; Humans; virus hepatitidy B; Tenofovir; prekurzory léčiv; Phenol; Amides; Drug Discovery; mikrobiální testy citlivosti; Antiviral Agents; tenofovir; lidé